The Frequency and Severity of Gastrointestinal Symptoms in Rugby Players - Chantler, Sarah; Wood-Martin, Ruth; Holliday, Adrian; Davison, Glen; Crabtree, Daniel R.; Readhead, Clint; Jones, Ben (International Journal of Sports Medicine, 2024)
This study aimed to assess the self-reported frequency and severity of gastrointestinal symptoms (GIS) at rest and around rugby training and match play in male and female rugby union players. An online questionnaire was sent to registered rugby union players (sevens or fifteens). Thirteen GIS were assessed alongside perceptions of appetite around rugby and rest using Likert and visual analog scales. Questions investigating a range of medical and dietary factors were included. Three hundred and twenty-five players (male n=271, female n=54) participated in the study. More frequent GIS (at least one GIS experienced weekly/more often) was reported by players at rest (n=203; 62%) compared to around rugby (n=154; 47%). The overall severity of GIS was low (mild discomfort), but a portion of players (33%) did report symptoms of moderate severity around rugby. Female players reported more frequent and severe symptoms compared to male counterparts (p<0.001). Self-reported appetite was significantly lower after matches compared to training. There were no dietary or medical factors associated with GIS severity scores. This study describes GIS characteristics in male and female rugby union players. Half of the players assessed experienced some form of GIS that may affect nutrition, training, or performance, and should thus be a consideration for practitioners supporting this cohort.
Keywords: rugby; gastrointestinal symptoms; appetite; sports